2015
DOI: 10.3758/s13415-014-0331-6
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomical delineation of agentic and affiliative extraversion

Abstract: Extraversion is a fascinating personality dimension that consists of two major components, agentic extraversion and affiliative extraversion. Agentic extraversion involves incentive motivation and is expressed as a tendency toward assertiveness, persistence, and achievement. Affiliative extraversion involves the positive emotion of social warmth and is expressed as a tendency toward amicability, gregariousness, and affection. Here we investigate the neuroanatomical correlates of the personality traits of agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…Metabolism in the orbitofrontal cortex also scales with combined measures of agentic and affiliative extraversion [21]. Agentic extraversion is uniquely correlated with the amount of gray matter in five additional brain regions – the left parahippocampal gyrus, left cingulate gyrus, left caudate, and left precentral gyrus [14]. This study also revealed intriguing gender differences, with only men showing correlations in the right nucleus accumbens.…”
Section: Extraversionmentioning
confidence: 93%
See 3 more Smart Citations
“…Metabolism in the orbitofrontal cortex also scales with combined measures of agentic and affiliative extraversion [21]. Agentic extraversion is uniquely correlated with the amount of gray matter in five additional brain regions – the left parahippocampal gyrus, left cingulate gyrus, left caudate, and left precentral gyrus [14]. This study also revealed intriguing gender differences, with only men showing correlations in the right nucleus accumbens.…”
Section: Extraversionmentioning
confidence: 93%
“…These components are measured using separate personality scales and factors (for details see [10]), and modulate emotional and behavioral responses to incentive reward and social cues [12] [13]. These sub-components are mechanistically dissociable with agentic and affiliative extraversion relating to the response to dopamine and mu-opiate drugs, respectively [10] [14]. Pharmacologically, trait measures of extraversion predict responses to drugs that act through dopamine mechanisms such as bromocriptine, a D2 receptor agonist that causes greater eyeblink and prolactin responses in individuals with high trait extraversion [15], and methylphenidate, which causes greater context-related cue conditioning in individuals with high trait extraversion [16].…”
Section: Extraversionmentioning
confidence: 99%
See 2 more Smart Citations
“…In so doing, extraversion has been shown to be positively related to regional volume of the medial orbitofrontal cortex (DeYoung et al, 2010; Grodin and White, 2015), nucleus accumbens (Grodin and White, 2015), left temporal cortex, dorsolateral prefrontal cortex (DLPFC), anterior cingulate (Grodin and White, 2015; Kapogiannis et al, 2013), and left amygdala (Omura et al, 2005); and negatively related to regional volume of the bilateral amygdala and parahippocampal (Lu et al, 2014), right middle temporal gyrus, inferior frontal gyrus (Bjørnebekk et al, 2013; Wright et al, 2006) and right temporoparietal junction (Forsman et al, 2012). On the other hand, also using VBM analysis, neuroticism has been positively associated with volume of right cerebellum (Lu et al, 2014), middle temporal gyrus and cingulate cortex (DeYoung et al, 2010; Omura et al, 2005); and negatively correlated with right orbitofrontal cortex, DLPFC, amygdala and precentral gyrus (DeYoung et al, 2010).…”
Section: Introductionmentioning
confidence: 99%